Eksistensi dan Pewarisan Budaya Tuku dalam Masyarakat Pulau Ndao (Orang Ndao) Kabupaten Rote Ndao Ntt - Luji, Daud Saleh (UI Scholars Hub, 2020)
On Ndao Island, Ndao Nuse Subdistrict, Rote Ndao Regency, the people have two prominent skills and have become the livelihoods of the people on the island, namely weaving skills (manènnu) and craftsmen or silversmiths (tuku). The two skills of the above Ndao island community are passed on by parents with informal and non-formal education patterns, but the two cultures experience different developments. Manènnu culture is still developing today among women while tuku culture is almost extinct. To find out the existence and cause of near extinction of Tuku’s skills, this research was carried out with the formulation of the problem as follows: 1) how the existence of silver or tuku craftsmen on Ndao Island; 2) what is the cause of the almost endangered skill of silversmiths or tuku in Ndao Island; 3) how are the efforts of the people of Ndao Island to pass down the culture of silversmiths or tuku to young generation. This study aims: 1) to find out the existence of silver or tuku craftsmen on Ndao Island; 2) to find out the cause of the almost endangered skill of silversmiths or tuku in Ndao Island; 3) to know the efforts of the people of Ndao Island to pass down the culture of silversmiths or tuku to their young generation. The method used in this study is a qualitative research method with interview and observation techniques for data collection. From the results of data analysis it can be concluded the following matters: First, there is an effort of cultural inheritance in society but does not use the right pattern. Second, the lack of interest in the younger generation to learn tuku. Third, the existence of cultural assimilation is the inclusion of a new method of fishing that is using a large trawl boat with a large trawl type so that many young people from Ndao Island who do not want to learn tuku skills and prefer to be subordinates to lampara boats whose income is actually far below the skills of tuku. Besides that, there are many people who pursue seaweed cultivation, the Fourth. The more difficult the silver raw materials in the community. The fifth pattern of cultural inheritance is not done well and well organized.